Urinary iodine concentration and its associations with thyroid function in pregnant women of Shanghai - Wu, Yiming; Yang, Jie; Su, Qing; Gu, Hongxia; Qin, Li (Frontiers in Endocrinology, 2023)
Objective To assess the iodine status and its associations with thyroid function in pregnant women of Shanghai. Methods In this cross-sectional study, a total of 562 pregnant women were enrolled from January to December 2021. Both serum thyroid-stimulating hormone (TSH), free triiodothyronine (FT3), free thyroxine (FT4), thyroid peroxidase antibody (TPOAB), thyroglobulin antibody (TGAB), and urinary iodine concentration (UIC) were detected. Participants were divided into four groups based on their UIC values. Correlation analysis was used to investigate the association between UIC and thyroid function-associated parameters. Results The median UIC of the pregnant women studied was 158.25µg/L (interquartile range [IQR] 90.15, 245.65µg/L). Among all the subjects, 45.55% had iodine deficiency according to the World Health Organization (WHO) criteria, and 15.65% had thyroid autoimmunity. FT3, FT4, TSH, TPOAB and TGAB levels were not different among different UIC groups (P > 0.05). UIC and TSH were negatively correlated (r=-0.127, p=0.043) in UIC<150 µg/L group. In the group with UIC 250- 499 µg/L, UIC was positively correlated with total T4 (TT4), total T3 (TT3) and TPOAB (r= 0.228, p=0.022, r=0.208, p= 0.039, r=0.190, p=0.042, respectively). A negative correlation between UIC and TPOAB values was observed in TPOAB-positive (+) pregnant women (r=-0.384, p=0.012). The prevalence of isolated hypothyroxinemia in UIC<150 µg/L group was significantly higher than that of other groups(p=0.033). The relationship between the prevalence of thyroid diseases and UIC embodied a U-shaped curve. Conclusion Pregnant women on Chongming Island of Shanghai were iodine sufficient during the second trimester, but iodine deficiency was still prevalent. Both low and high gestational iodine status was related to thyroid function and autoimmunity. Optimal iodine nutrition status during gestation was important.